A robotics wheelchair for crowded public environment. - Prassler, E. (IEEE Robotics and automation magazine)
Describes the robotic wheelchair MAid (Mobility Aid for Elderly and Disabled People). MAid's task is to support and transport people with limited motion skills. It is based on a commercial wheelchair that has been equipped with an intelligent control and navigation system. Conversations with disabled and elderly people and with their physicians indicate that the automatic functions desired in a robotic wheelchair do not include following walls or passing doorways, but do include navigation in narrow, cluttered environments and through wide, crowded areas. MAid performs these functions